(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2024)
This article generally discusses the Arab Spring events that took place in Libya in 2011. From this general discussion, the discussion then elaborates on several issues, namely the living conditions of Libya before the revolution, the role of youth and social media in the revolutionary movement, the process of the revolution and the impact of revolution to social and political life in Libya. This research uses historical research methods or historical methods which include the heuristic process, criticism, interpretation, and historiography. Based on the research results, it is concluded that the conditions of social and political life during Gaddafi’s reign influenced the emergence of the revolutionary movement in 2011. Youth and social media have a vital and effective role to play in pursuing the revolutionary movement in Libya. The revolutionary process carried out by the people, led to civil war in Libya, namely between the opposition and the pro Gaddafi camp. The impact of the revolution on socio-political life is that there is a life that is more democratic than before, but there are new problems related to security and unity in Libya.